Predictive value of inflammatory marker PLR in prostate cancer - Junhao Sun; Yu Song; Yunfei Tan; Limin Ma; Huyang Xie (BMC Urology)
Abstract Purpose This study aims to investigate the correlation between inflammatory markers and prostate cancer with a good-quality predictive model. Methods The original dataset was randomly split into a training set (70%) and a validation set (30%). Logistic regression was used to examine the related risk factors within the training set. ROC curve analysis was conducted to evaluate the discriminative ability of risk factors for PCa. The accuracy and performance of the prediction model were evaluated using the clinical decision curve and 10-fold cross-validation. The diagnostic value of the model was compared across various PSA regions in the entire dataset. The nomogram was employed to illustrate the predictive model. Additionally, we analyzed the corresponding variables and the relationship between the International Society of Urological Pathology (ISUP) grading of PCa. Results Age, prostate volume (PV), total PSA (tPSA), (f/t) PSA, and platelet-to-lymphocyte ratio were identified as independent risk factors for prostate cancer. The predictive model utilizing these parameters has shown significant clinical advantage, stability, and elevated diagnostic efficacy within the PSA range of 4–20 ng/mL. Additionally, significant differences in tPSA and PV were observed among PCa patients with varying ISUP grades. Conclusion PLR can serve as a predictive indicator for prostate cancer and, when integrated with additional clinical data, can enhance the detection rate of prostate cancer. Moreover, there was no correlation between PLR and the ISUP grade of PCa.